THE INFLUENCE OF MOTIVATION AND COMPETENCE ON THE PERFORMANCE OF BANK MANDIRI EMPLOYEES OF MEGA LAND PEMATANGSIANTAR BRANCH OFFICE - Yoan Hendrawan Junpridan Saragih (SEAN Institute, 2022)
This study aims to determine the effect of motivation and competence on the performance of Bank Mandiri Mega Land Pematangsiantar Branch Office employees. The results of this research can be a contribution of thought to Bank Mandiri in an effort to improve employee performance through an in-depth study of Employee Motivation, Competence and Performance. The research method used is descriptive analysis and verification. The collection of data used is an interview using a questionnaire accompanied by observation and literature techniques. The sampling technique uses saturated sampling or census techniques. Field data collection was carried out in 2019. Data analysis techniques used the SPSS 22 program. The results of the descriptive analysis show that in general motivation and competence fall into the unfavorable category. The results of the verification analysis show that motivation and competence affect performance. Either partially or simultaneously. Partially the motivational variable is more dominant in influencing employee performance at Bank Mandiri Mega Land branch office than the competency variable.